2015
DOI: 10.4236/fns.2015.62027
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Germ: An Overview on Nutritional Value, Antioxidant Potential and Antibacterial Characteristics

Abstract: Wheat germ is a by-product derived from the wheat milling industry. Defatted wheat germ is the main by-product of the wheat germ in the oil extraction process. This study aims at development of efficient and low cost processing methods to transform these residues in added value co-product. In this study, wheat germ was analysed for its proximate composition, fatty acid composition, physical and chemical characteristics of wheat germ oil. The basic chemical composition analyses revealed high values of dry matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 23 publications
(30 reference statements)
8
47
1
Order By: Relevance
“…The WG comprised 13.2% moisture, 9.0% fat, 5.9% ash, 24.1% protein, and 48.2% carbohydrate. The above results are similar to other studies [1,4,38]. Values are mean ± standard deviations of n = 3.…”
Section: Simulation Of the Inlet Air Temperature Of Fbdsupporting
confidence: 92%
See 1 more Smart Citation
“…The WG comprised 13.2% moisture, 9.0% fat, 5.9% ash, 24.1% protein, and 48.2% carbohydrate. The above results are similar to other studies [1,4,38]. Values are mean ± standard deviations of n = 3.…”
Section: Simulation Of the Inlet Air Temperature Of Fbdsupporting
confidence: 92%
“…It is rich in many nutrients and bioactive compounds, thus, it is widely applied in bread, snack foods, and breakfast cereals [1]. Since WG contains phenolic compounds, it is also used to produce valuable antioxidant supplements [2].…”
Section: Introductionmentioning
confidence: 99%
“…The extracts prepared from WGO has tendency to reduce 2, 2‐diphenyl‐1‐picrylhydrazyl or DPPH free radicals and this tendency is comparable with those of synthetic antioxidants such as butylated hyroxytoluence (BHT) and butylated hydroxyanisole (BHA) . The antibacterial activity of WGO extracts have also been tested against pathogenic bacteria and it was observed that L. monocytogenes and S. aureus were the most sensitive strains, followed by E. coli and S. enterica . It has been observed that WGO is an excellent source of natural antioxidants, bioactives, and antimicrobial compounds.…”
Section: The Functional Activities and Utilization Areas Of Wheat Germentioning
confidence: 89%
“…It is expected because phenolic substances are concentrated in the bran and germ fractions of wheat that are removed during the milling process. Moreover, Mahmoud et al . reported the radical scavenging activity of DWG was close to that of synthetic antioxidants (BHA, BHT).…”
Section: Resultsmentioning
confidence: 99%
“…The ABTS assay was used according to Ravikumar et al . and Mahmoud et al . with some modifications to determine the ABTS radical scavenging activity of the extracts.…”
Section: Methodsmentioning
confidence: 99%